CONTRASTIVE MEIREI BUN WITH IMPERATIVE DIVERSITY: ‘JAPANESE AND INDONESIA’ - Latif Jaohari, Abdul; Gayatri Ranadireksa, Dinda (International Journal of Psychosocial Rehabilitation, 2020)
Language is not just a sequence of sounds that can be digested empirically but also rich with nonempirical meanings (Alwasilah, 2007: 14). Thus, language is a vital means of expressing and embodying the contents of thoughts, facts, and reality in our lives. Because with language, the consideration of truth and justice can be done. The purpose of this article is thus to provide a contrasting comparison between Japanese and Indonesian language by looking at Meirui Bun in order to capture the imperative diversity. The study recognizes the role of language as a tool of communication as well as interaction between members of the community. It can be concluded that despite the vast differences, it is common for both to have longer imperatives, which leads to indirect imperative speech.